Upaya Meningkatkan Kemampuan Kognitif Anak Usia 5-6 Tahun Melalui Permainan Balok Angka di RA An-Nida - Sari Harahap, Hotma; Khadijah, Khadijah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The poor degree of cognitive capacity to recognise numbers in Ra'an-nida was the driving force behind this investigation. The outcomes of the preliminary observations demonstrate this. youngsters's cognitive capacity to recognise numbers is still developing; in Ra an-nida, 70% of youngsters between the ages of 5 and 6 have little understanding of what cognitive ability is. The purpose of this study is to determine how number block media use can enhance children's cognitive development in number recognition, how cognitive abilities of children are prior to using number blocks, and how the number block process can enhance the cognitive abilities of children in Ra'an-nida who are between the ages of five and six. Ten boys and seven girls made up the total number of participants in this class action research study. Techniques for gathering data: In this study, documentation and observation are used to gather data. The percentage methodology is the data analysis method used in this study. According to study done in Ra'an-nida, children between the ages of 5 and 6 had a cognitive ability percentage of 29%, with an average value of 2. In the first cycle, the percentage was 58%. exhibiting an average value of 2.64 and developing criteria. In cycle II, there was an improvement in the cognitive development of children aged 5–6 years, with a 100% percentage and an average score of 3.52 with very excellent development requirements..